 2. with co-separable core.

Below it is shown that

FCD

(

A

;

B

)

are complete lattices for every sets

A

and

B

. We will apply

lattice operations to subsets of such sets without explicitly mentioning

FCD

(

A

;

B

)

.

Theorem 6.37.

FCD

(

A

;

B

)

is a complete lattice (for every sets

A

and

B

). For every

R

2

P

FCD

(

A

;

B

)

and

X

2

P

A

,

Y

2

P

B

1.

X

[

F

R

]

Y

, 9

f

2

R

:

X

[

f

]

Y

;

2.

h

F

R

i

X

=

F

fh

f

i

X

j

f

2

R

g

.

Proof.

Accordingly [

26

to prove that it is a complete lattice it's enough to prove existence of all

joins.

2.

X

=

def

F

fh

f

i

X

j

f

2

R

g

. We have

;

= 0

F

(

Dst

f

)

;

(

I

[

J

) =

G

fh

f

i

(

I

[

J

)

j

f

2

R

g

=

G

fh

f

i

I

t h

f

i

J

j

f

2

R

g

=

G

fh

f

i

I

j

f

2

R

g t

G

fh

f

i

J

j

f

2

R

g

=

I

t

J:

So

h

h

i

=

for some funcoid

h

. Obviously

8

f

2

R

:

h

w

f :

(6.5)

And

h

is the least funcoid for which holds the condition (

6.5

). So

h

=

F

R

.

1.

X

[

F

R

]

Y

, "

Dst

f

Y

u h

F

R

i

X

=

/ 0

F

(

Dst

f

)

, "

Dst

f

Y

u

F

fh

f

i

X

j

f

2

R

g

=

/ 0

F

(

Dst

f

)

,

9

f

2

R

:

"

Dst

f

Y

u h

f

i

X

=

/ 0

F

(

Dst

f

)

, 9

f

2

R

:

X

[

f

]

Y

(used proposition

4.194

).

In the next theorem, compared to the previous one, the class of innite joins is replaced with

lesser class of nite joins and simultaneously class of sets is changed to more wide class of lters.

Theorem 6.38.

For every

f ; g

2

FCD

(

A

;

B

)

and

X 2

F

(

A

)

(for every sets

A

,

B

)

1.

h

f

t

g

iX

=

h

f

iX t h

g

iX

;

2.

[

f

t

g

]=[

f

]

[

[

g

]

.

Proof.

1. Let

X

=

def

h

f

iX t h

g

iX

;

Y

=

def

h

f

¡

1

iY t h

g

¡

1

iY

for every

X 2

F

(

A

)

,

Y 2

F

(

B

)

. Then

Y u

X

=

/ 0

F

(

B

)

, Y u h

f

iX

=

/ 0

F

(

B

)

_ Y u h

g

iX

=

/ 0

F

(

B

)

, X u h

f

¡

1

iY

=

/ 0

F

(

A

)

_ X u h

g

¡

1

iY

=

/ 0

F

(

A

)

, X u

Y

=

/ 0

F

(

A

)

:

So

h

= (

A

;

B

;

;

)

is a funcoid. Obviously

h

w

f

and

h

w

g

. If

p

w

f

and

p

w

g

for some funcoid

p

then

h

p

iX w h

f

iX t h

g

iX

=

h

h

iX

that is

p

w

h

. So

f

t

g

=

h

.

2.

X

[

f

t

g

]

Y , Y u h

f

t

g

iX

=

/ 0

F

(

B

)

, Y u

(

h

f

iX t h

g

iX

) =

/ 0

F

(

B

)

, Y u h

f

iX

=

/ 0

F

(

B

)

_

Y u h

g

iX

=

/ 0

F

(

B

)

, X

[

f

]

Y _ X

[

g

]

Y

for every

X 2

F

(

A

)

,

Y 2

F

(

B

)

.

Denition 6.39.

GR

f

=

def

F

2

P

(

Src

f

Dst

f

)

j "

FCD

(

Src

f

;

Dst

f

)

F

w

f

.

Denition 6.40.

xyGR

f

=

def

f

(

Src

f

;

Dst

f

;

F

)

j

F

2

GR

f

g

.

Remark 6.41.

xyGR

f

is a set of Rel-morphisms.

6.5 More on composition of funcoids

Proposition 6.42.

[

g

f

]=[

g

]

h

f

i

=

h

g

¡

1

i

¡

1

[

f

]

for every composable funcoids

f

and

g

.

6.5 More on composition of funcoids

101